2004
DOI: 10.1111/j.1467-8527.2004.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Making Connections: Teachers’ Use of Children's Prior Knowledge in Whole Class Discourse

Abstract: This paper investigates teachers' use of prior knowledge in whole class teaching contexts and draws on data from an ESRCfunded study. The paper explores how teachers conceptualise prior knowledge, principally as that which has been taught in school. It demonstrates strong teacher awareness of how the teaching under consideration fits with learning previously undertaken by the class, but less awareness of how the learning might build on prior learning outside school. The paper considers how teachers make connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…According to Collins (1996), teachers assess and support children's learning by talking to them and listening to what they say and for pupils to be successful and make the most of learning opportunities, it is important that they become active participants in classroom discussion. Collins' view is in line with the views expressed earlier, that conversations between children and adults significantly aid cognitive development (Hedegaard, 1999;Myhill, 2003;Myhill & Brackley, 2004;Ogden, 2000;Vygotsky, 1986).…”
Section: Interaction -Learning From Each Other and From The Teachersupporting
confidence: 76%
See 2 more Smart Citations
“…According to Collins (1996), teachers assess and support children's learning by talking to them and listening to what they say and for pupils to be successful and make the most of learning opportunities, it is important that they become active participants in classroom discussion. Collins' view is in line with the views expressed earlier, that conversations between children and adults significantly aid cognitive development (Hedegaard, 1999;Myhill, 2003;Myhill & Brackley, 2004;Ogden, 2000;Vygotsky, 1986).…”
Section: Interaction -Learning From Each Other and From The Teachersupporting
confidence: 76%
“…Research into the nature of classroom discussion has shown that it is dominated by statements and questions from the teacher (Burns & Myhill, 2004;Myhill & Brackley, 2004). Burns and Myhill (2004) argue that this kind of discourse situation does not support or scaffold pupils' learning because the interaction is largely a case of pupils participating upon request.…”
Section: Interaction -Learning From Each Other and From The Teachermentioning
confidence: 99%
See 1 more Smart Citation
“…In a school setting, the interaction between the teacher and the learner is essentially dialogical (ibid) so language is one of the tools of mediation between the subject to be learnt and the learner. There has been much research into the role of talk in primary schools in the UK which is based on the premise of teacher and student talk as the mediating tool in the construction of knowledge (Mercer, 1995(Mercer, , 2000Myhill, 2004;Myhill & Warren, 2005). Structured classroom talk between teacher and students guides the construction of knowledge (Alexander, 2001(Alexander, , 2004Mercer, 1995Mercer, , 2000Mercer & Littleton, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…(p. 92) Of course, this assumes that the learner has sufficient conscious awareness to make those comparisons and inter-relationships. The point is that the teacher must take some responsibility for actually pointing to the connections that need to be made and in helping their students work through these (see Myhill & Brackley, 2004). Mercer (1995) argues along similar lines in making the case for a continuity of experience for students:…”
mentioning
confidence: 96%